“La Tejería” Festival: influence on the vernacula architecture of Poaló. Píllaro. Ecuador - Cardet García, Javier (2021)
The importance of vernacular architecture was analyzed, as an expression of the identity of the rural habitat; understanding the relationship between the context and cultural practices. The research was carried out in the San José de Poaló parish, in the Píllaro canton with the aim of analyzing the influence of the popular festival on vernacular architecture. Based on the definition of traditional architecture as part of tangible heritage, the study was approached with a qualitative approach, through observation cards, which described the formal, functional configuration, and the spatial conceptions expressed in its popular festival: “La Trajería” Finally, a proposal of guidelines was raised, for the conservation of customs and their incidence in vernacular constructions.